Aplikasi dan Sosialisasi PSAK 109 tentang Zakat, Infak dan Sedekah pada Organisasi Pengelola Zakat (OPZ) sebagai Wujud Transformasi Digital dan Profesionalisme dalam Akuntansi untuk Generasi Muda - Ridho, Ali; Irsan, M. Syah (KANGMAS: Karya Ilmiah Pengabdian Masyarakat, 2024)
This a This activity is a manifestation of the duties and responsibilities of lecturers in implementing the program Tri dharma perguruan tinggi, which consists of education, research and community service, as mandated by law. The aim of this activity is to reduce the burden on the Government in order to overcome the high unemployment rate among vocational school graduates in Indonesia, with a focus on SMK N 25 South Jakarta. Mismatch of graduate skills with market needs, is one of the main causes of high unemployment rates. The implementation of this community service is carried out using a contextual model or approach that connects market needs with the skills provision of students SMK N 25 South Jakarta. A team of lecturers from Mercu Buana University, Jakarta, Faculty of Economics and Business, held socialization training and application of PSAK 109 regarding zakat, infaq and alms accounting at zakat management organizations (OPZ) as a form of digital transformation and professionalism in accounting for the younger generation, for students SMK N 25 South Jakarta, with stages: preparation, planning, coordination, providing direct explanations and training at school, and evaluating implementation results. The results of the implementation showed that as many as 90% (ninety percent) of the students who took part in this activity understood or understood well the theme that had been presented by the Lecturer Team at the Faculty of Economics and Business, Mercu Buana University, Jakarta. This training has succeeded in equipping students with relevant and up-to-date skills, thereby reducing the gap between vocational education and labor market needs.